Repetitive stability study of remdesivir/cyclodextrin complex on the international space station - György Dormán; Balázs Buchholcz; István Puskás; Pál Szabó; Erzsébet Varga; Lajos Szente; György M. Keserű; Ferenc Darvas (Scientific Reports)
Abstract Stability assessment of drugs in space is particularly important for future missions. In space there are multiple factors, such as the variability of the conditions (radiation, microgravity, vacuum etc.) that could affect the reliability and reproducibility of the data. Therefore, we investigated the stability of an anti-Covid drug formulation, Remdesivir (RDV) sulfobutylether-beta-cyclodextrin (SBECD) complex, in two separate flight experiments on the International Space Station (ISS). While HPLC/MS studies revealed no degradation of the cyclodextrin excipient in any of the samples investigated in both missions, RDV purity analysis of the RDV/SBECD complex after the first mission revealed different stabilities and altered degradation in space and on Earth. This latter interesting finding was not supported by the second mission, where no differences in the drug stabilities were identified. This anomaly highlighted the importance of standardization together with increased control of the variable parameters during the entire space missions and the terrestrial control experiments.